2021
DOI: 10.1016/j.compbiomed.2021.104293
|View full text |Cite
|
Sign up to set email alerts
|

Network pharmacology and RNA-sequencing reveal the molecular mechanism of Xuebijing injection on COVID-19-induced cardiac dysfunction

Abstract: Background Coronavirus disease 2019 (COVID-19) is an emerging infectious disease caused by severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). Up to 20%–30% of patients hospitalized with COVID-19 have evidence of cardiac dysfunction. Xuebijing injection is a compound injection containing five traditional Chinese medicine ingredients, which can protect cells from SARS-CoV-2-induced cell death and improve cardiac function. However, the specific protective mechanism of Xuebijing injection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 72 publications
(55 reference statements)
0
14
0
Order By: Relevance
“…To screen the potential bioactive compounds from Fuzi, two important parameters including oral bioavailability (OB) and drug-likeness (DL) that are associated with drug absorption, distribution, metabolism, and excretion were used. The threshold for screening bioactive compounds was set as OB ≥ 30 and DL ≥ 0.18 17 . Because some compounds that did not pass the threshold might show significant pharmacological effects as well, compounds that were reported to exhibit strong pharmacological effects yet not meet the threshold of OB or DL were also used.…”
Section: Methodsmentioning
confidence: 99%
“…To screen the potential bioactive compounds from Fuzi, two important parameters including oral bioavailability (OB) and drug-likeness (DL) that are associated with drug absorption, distribution, metabolism, and excretion were used. The threshold for screening bioactive compounds was set as OB ≥ 30 and DL ≥ 0.18 17 . Because some compounds that did not pass the threshold might show significant pharmacological effects as well, compounds that were reported to exhibit strong pharmacological effects yet not meet the threshold of OB or DL were also used.…”
Section: Methodsmentioning
confidence: 99%
“…Network-based pharmacology to explore the molecular targets of the action of Wenxin Keli (WXKL) in the treatment of atrial fibrillation, it was found that these targets were closely related to inflammatory response, oxidative stress response, and immune regulation, and CCL2 was one of the main targets of its action ( 157 ). Bioinformatics analysis suggests that hemiphilin injection may exert a potential protective effect against neocoronary pneumonia, especially COVID19-induced cardiac insufficiency, by targeting seven Hub genes, including CCL2 and CXCL8, to inhibit oxidative stress, prevent atherosclerotic plaque formation, and suppress inflammation and apoptosis ( 158 ).…”
Section: Drug Studies Based On the Ccl2-ccr2 Axis For The Treatment O...mentioning
confidence: 99%
“…He et al . identified the therapeutic effect of Xuebijing injection on COVID-19-induced cardiac dysfunction using bioinformatics analysis ( He et al, 2021 ). Xuebijing injection indicated oxidative stress inhibition, atherosclerotic plaque prevention, inflammatory repression and apoptosis by targeting 7 central hub genes including CCL2, CXCL8, FOS, IFNB1, IL-1A, IL-1B, SERPINE1 that have protective mechanism on COVID-19-induced cardiac dysfunction.…”
Section: Network Pharmacologymentioning
confidence: 99%